NEPSC2, the North Ecliptic Pole SCUBA-2 survey: 850-μm map and catalogue of 850-μm-selected sources over 2 deg2. Issue 4 (27th August 2020) - Shim, Hyunjin; Kim, Yeonsik; Lee, Dongseob; Lee, Hyung Mok; Goto, Tomo; Matsuhara, Hideo; Scott, Douglas; Serjeant, Stephen; Ao, Yiping; Barrufet, Laia; Chapman, Scott; Clements, David L; et al.
ABSTRACT: We present an 850- μ m mosaic map and extracted catalogue of submillimetre sources in the extended North Ecliptic Pole (NEP) region over about 2 deg 2 . The 850- μ m map is constructed using newly obtained observations by SCUBA-2 at the East Asian Observatory's James Clerk Maxwell Telescope, carried out using the observatory's large programme opportunities. The recent 850- μ m survey has extended the submillimetre data coverage by almost a factor of 4 compared to previous surveys, with a depth of σ _rms = 1.0 –2.3 mJy beam^-1 . The catalogue contains 549 sources selected above a significance level of 4σ, where the false-detection rate is 10 per cent; a higher threshold of 4.5σ is required in order to achieve a false-detection rate below 3 per cent, which results in 342 sources being selected. Despite the large spatial variation of the noise, the deboosted flux density of sources is comparable to results from the SCUBA-2 Cosmology Legacy Survey, which covered the central 0.6 deg 2 of our survey area with better sensitivity. We construct the source counts at 850 μ m, finding results in agreement with other 850- μ m surveys in cosmological blank fields over S 850 = 4–15 mJy. We find a slight excess of bright galaxies (S_850 15 mJy), which can be considered to be at z_phot = 2 –4. The 850- μ m data add valuable long-wavelength information to mid-infrared-selected sources from the AKARI NEP-deep and NEP-wide surveys, which will be helpful in preparing for future near-infrared to millimetre wavelength observations in the NEP region. Our 850- μ m mosaic map and source catalogue will be made publicly available.